Reticulon Homology Domain-Containing Proteins and ER-Phagy - Manuela D’Eletto; Serafina Oliverio; Federica Di Sano (Frontiers in Cell and Developmental Biology, 2020)
The endoplasmic reticulum (ER) is a dynamic membrane system comprising different and interconnected subdomains. The ER structure changes in response to different stress conditions through the activation of a selective autophagic pathway called ER-phagy. This represents a quality control mechanism for ER turnover and component recycling. Several ER-resident proteins have been indicated as receptors for ER-phagy; among these, there are proteins characterized by the presence of a reticulon homology domain (RHD). RHD-containing proteins promote ER fragmentation by a mechanism that involves LC3 binding and lysosome delivery. Moreover, the presence of a correct RHD structure is closely related to their capability to regulate ER shape and morphology by curvature induction and membrane remodeling. Deregulation of the ER-selective autophagic pathway due to defects in proteins with RHD has been implicated in several human diseases, infectious and neurodegenerative diseases in particular, as well as in cancer development. While the molecular mechanisms and the physiological role of ER-phagy are not yet fully understood, it is quite clear that this process is involved in different cellular signaling pathways and has an impact in several human pathologies.